Polyurethane Thermosets Using Lipidic Poly(α‐Hydroxyketone). (12th November 2019) - Briou, Benoit; Vu, Nam Duc; Caillol, Sylvain; Robin, Jean‐Jacques; Duguet, Nicolas; Lemaire, Marc; Etienne, Pascal; Bonnet, Laurent; Lapinte, Vincent
Abstract: Lipidic polyols based on α‐hydroxyketone reactive groups were investigated for polyurethane thermosets. The reactivity of this peculiar secondary alcohol group in triacylglycerol structure was compared, without use of catalyst, to that of poly(1, 2‐diol) triacylglycerol and castor oil to demonstrate the influence of ketone in the α position of the alcohol group in the presence of HDI for the urethanization rate. The kinetic effect of the ketone group was also studied on various lipidic architectures: mono(α‐hydroxyketone) ester, di(α‐hydroxyketone) diester and tri(α‐hydroxyketone) triacylglycerol. The presence of hydrogen bonds in the network coming from urethane, residual alcohol, and ketone in hard segments of PU was discussed and correlated with the thermal stability and the soft mechanical properties of the resulting polyurethane thermosets.